2009
DOI: 10.1254/jphs.08189fp
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of a Mixture of Aloe vera and Silybum marianum Against Carbon Tetrachloride–Induced Acute Hepatotoxicity and Liver Fibrosis

Abstract: Abstract. The hepatoprotective effects of ACTIValoe ® N-931 complex, a mixture of Aloe vera and Silybum marianum, against acute and chronic carbon tetrachloride (CCl 4 )-induced liver injuries were investigated. Acute hepatotoxicity was induced by intraperitoneal injection of CCl 4 (50 μl / kg), and ACTIValoe ® N-931 complex at 85, 170, and 340 mg / kg was administered orally 48, 24, and 2 h before and 6 h after injection of CCl 4 . Hepatotoxicity was assessed 24 h after CCl 4 treatment. Liver fibrosis was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 38 publications
(27 reference statements)
2
21
0
Order By: Relevance
“…In this study Silybum marianum was used for treatment of lipid accumulation in fatty liver induction by tamoxifen. Because SME have a strong protection effect against multiple drugs (10,22), applying SME in TMX-treated rats decreased liver enzymes activities close to normal levels. In addition, the rise of the serum total protein indicated that liver function was improved in the presence of SME.…”
Section: Discussionmentioning
confidence: 97%
“…In this study Silybum marianum was used for treatment of lipid accumulation in fatty liver induction by tamoxifen. Because SME have a strong protection effect against multiple drugs (10,22), applying SME in TMX-treated rats decreased liver enzymes activities close to normal levels. In addition, the rise of the serum total protein indicated that liver function was improved in the presence of SME.…”
Section: Discussionmentioning
confidence: 97%
“…Dose of CCl 4 was selected on the basis of a 0.5 ml CCl 4 /kg rat weight diluted in olive oil (1:1 dilution) intraperitonally injection twice per week concentration at which caused oxidative stress and hepatotoxicity administered. 13 Group III (10% CP): the rats received tab water and fed with 10% CP containing diet supplementation. Group IV (0.5 ml CCl4/kg BW + 10% CP): the rats received 0.5 ml CCl 4 /kg rat weight intraperitonally injection twice per week and fed with 10% CP containing diet supplementation.…”
Section: Experimental Designmentioning
confidence: 99%
“…In addition, single i.p. administration of CCl 4 induces histological changes including inflammatory cell infiltration in the mouse liver (Kim et al, 2009). Kupffer cell activation is a crucial event in hepatocyte injury induced by CCl 4 and activated Kupffer cells release cytokines such as TNF-α and IL-6, which are important factors for hepatocyte regeneration (Taub et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo mutagenicity of MeIQx in transgenic mice has also been reported in the liver (Itoh et al, 2000;. Carbon tetrachloride (CCl 4 ) is a potent hepatotoxicant in rodents, and single administration at higher doses causes extensive hepatocellular necrosis with inflammatory cell infiltration (Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%